Psychological Preparation of Students for Extreme Situations using Virtual Reality - Skorobogatova, T.N.; Margolin, A.D. (Extreme Psychology and Personal Safety, 2024)
The article considers the results of the study of psychological preparation of students - extreme profile psychologists for situations of special risk through special organized training using virtual reality. Subjects: 38 students aged 20 to 24 years, including 29 females. The subjects were randomly divided into control and experimental groups. Research methods: method "Forecast", method of differential diagnostics of depressive states by V.A. Zhmurov, method "Assessment of neuropsychic stress", diagnostics of slowing down of biological aging using the program "Anti-aging XXI" (T.N. Berezina). Methods of mathematical statistics: calculation of descriptive statistics, calculation of the Mann-Whitney U criterion, calculation of the Spearman correlation coefficient. Methods of experimental influence: seven VR simulators of different influences (flight simulator, depth, altitude, speed, darkness, etc.). Results. There is a relationship between motivation for activity in extreme conditions and personal resources: a direct relationship with the "achievement" resource and an inverse relationship with the risk level. The VR training we developed actualizes these resources. Increased achievements are ensured by the fact that respondents successfully complete tasks in extreme situations simulated in VR. Risk reduction is ensured by adaptation to extreme situations during the training. After the training, the subjects of the experimental group showed a significant decrease in the level of depression and an increase in the motivational and emotional components of readiness for action in an extreme situation. Conclusion: to increase motivation for activity in an extreme environment, it is necessary to increase the "achievement" resource, and for the "risk" resource, it is necessary to achieve its replacement with a conscious attitude to the situation. Virtual reality technologies have proven their effectiveness in increasing personal resources and preparing psychology students for activity in extreme conditions. В статье рассмотрены результаты исследования психологической подготовки студентов-психологов экстремального профиля к ситуациям особого риска посредством специально организованного тренинга с применением виртуальной реальности. Испытуемые: 38 студентов в возрасте от 20 до 24 лет, из них 29 - женского пола. Испытуемые были разделены на контрольную и экспериментальную группы случайным образом. Методы исследования: методика «Прогноз», методика дифференциальной диагностики депрессивных состояний В.А. Жмурова, методика «Оценка нервно-психического напряжения», диагностика замедления биологического старения с помощью программы «Антистарение XXI» (Т.Н. Березина). Методы математической статистики: вычисление описательных статистик, вычисление U-критерия Манна-Уитни, вычисление коэффициента корреляции Спирмана. Методы экспериментального воздействия: семь ВР-симуляторов разного воздействия (симулятор полета, глубины, высоты, скорости, темноты и др.). Результаты. Существует взаимосвязь между мотивацией к деятельности в экстремальных условиях и личностными ресурсами: прямая взаимосвязь с ресурсом «достижения» и обратная - с уровнем риска. Разработанный нами ВР-тренинг актуализирует эти ресурсы. Повышение достижений обеспечивается тем, что респонденты успешно выполняют задания в экстремальных ситуациях, моделируемых в ВР. Снижение риска обеспечивается адаптацией в процессе тренинга к экстремальным ситуациям. После тренинга у испытуемых экспериментальной группы достоверно снизился уровень депрессии и повысились мотивационный и эмоциональный компоненты готовности к действиям в экстремальной ситуации. Вывод: для повышения мотивации к деятельности в экстремальной среде необходимо повышать ресурс «достижения», а для ресурса «риск» нужно добиться смены его на осознанное отношение к ситуации. Технологии виртуальной реальности подтвердили свою эффективность для повышения личностных ресурсов и подготовки студентов-психологов к деятельности в экстремальных условиях.